ChemInform Abstract: Synergistic Stereoselective Organocatalysis with Indium(III) Salts. Issue 45 (23rd October 2014) - Gualandi, Andrea; Mengozzi, Luca; Wilson, Claire Margaret; Cozzi, Pier Giorgio
Abstract Several organocatalytic SN1‐type reactions from allylic, benzylic and benzhydrylic alcohols are promoted by In(III) salts.